Novel field trial for ocean alkalinity enhancement using electrochemically derived aqueous alkalinity - Savoie, Allison M.; Ringham, Mallory; Torres Sanchez, Carolina; Carter, Brendan R.; Dougherty, Sean; Feely, Richard A.; Hegeman, Dave; Herndon, Julian; Khangaonkar, Tarang; Loretz, Jeremy; Minck, Tyson; Pelman, Todd; et al. (Frontiers in Environmental Engineering, 2025)
Ocean alkalinity enhancement is a proposed method of marine carbon dioxide removal that enhances the ocean’s uptake of atmospheric carbon dioxide (CO2) and converts it to dissolved bicarbonate for long-term ocean storage. This method of marine carbon dioxide removal has been gaining attention for its potential to durably (10,000+ years) store large amounts of CO2 (Gt + where 1 Gt = 1 × 109 tons), while potentially ameliorating acidification in the vicinity of the alkalinity release. This study focuses on a novel release of electrochemically derived aqueous alkalinity into Sequim Bay, WA, through a previously established wastewater treatment plant (WWTP). This research was made possible through the collaboration of industry, academic, and federal partners, which enabled the establishment of an Ebb Carbon electrochemical mCDR system at the Pacific Northwest National Laboratory in Sequim, WA, for ocean alkalinity enhancement field trials. During these field trials, pH was measured across the WWTP system from the initial alkalinity dosing, throughout the WWTP, and at the outfall. We use the NBS scale for pH throughout this study as it is the scale used in discharge permit limits specified for WWTP and NPDES regulation and compliance monitoring. The background pHNBS of Sequim Bay seawater was between 7.5 and 7.7 for the November and February field tests. The mixing tank’s pHNBS was raised to the maximum value permitted for the WWTP (9.0) and maintained across the system (±0.2) during the outfall releases. At the outfall, the elevated pH and alkalinity was quickly diluted, such that the region with a measurable signal was limited to within ∼2.5 m of the discharge pipe. We were able to successfully monitor an increase in pHNBS across all four pulses of alkalinity-enhanced seawater discharge during the February 2025 field trial, with peak pHNBS values of 8.3 or 8.1, as recorded by outfall-adjacent YSI Exo 2 sonde and SAMI-pH sensors, respectively. The alkalinity-enhanced seawater did not measurably alter the surrounding waters’ temperature, salinity, turbidity, or oxygen. This study provides proof-of-concept for a conservative small-scale release of electrochemically generated alkalinity-enhanced seawater from a coastal outfall.